THE ROLE OF BIG DATA IN MARKETING 5.0 : A SYSTEMATIC LITERATURE REVIEW - Sri Sulistiya Wati; Moehammad Robith Nahdi; Sastiana Mandasari Fathonah; Wening Patmi Rahayu; Titis Shinta Dewi (Journal of Management Small and Medium Enterprises (SMEs), 2025)
In the context of marketing, society 5.0 has major implications that fundamentally change how businesses operate and interact with consumers. In marketing 5.0, the use of big data is crucial; technological developments that influence consumer behavior and increasing market competition necessitate an analysis of consumer habits to facilitate marketers in advertising their products. This research employs the Systematic Literature Review (SLR) method using the Watase Uake application to search for articles published from 2021 to 2024. Previous research indicates that big data and related technologies significantly impact marketing and business strategies, enhancing sales prediction accuracy, boosting company profits, and generating innovative digital content. Keywords: Bigdata; Digital Marketing; Systematic Literature Review